Genetics of dual resistance to african stem borer, busseola fusca and spotted stem borer, Chilo partellus in sorghum - Phyllis, W. Muturi; Mgonja, M.; Rubaihayo, P. (Springer Link, 2021)
African stem borer, Busseola fusca Fuller (Noctuidae) and spotted stem borer, Chilo partellus Swinhoe (Crambidae) cause more than 40 % of grain yield loss in cereals and bothpests co-exist in mid-altitudes in Kenya. Development of sorghum with dual resistance to B. fusca and C. partellus has been difficult due to the inadequate understanding of inheritance of resistance traits to the two species. The objective of this study was to investigate the genetics of dual resistance to the two insect species in sorghum. Thirty sorghum populations derived from crossing sorghum lines with varying levels of resistance to the two insect species were studied. The experiments were conducted in two separate sites at Embu and Kiboko in Kenya with two replications per site. North Calorina Design II mating design was used. Artificial infestation with first instar neonates of each pest species was done at 30 days after planting in both sites. Data collected included sorghum damage due to the two borer species and agro-morphological traits. Genetic analyses were performed using line x tester method using Genstat statistical software. Data analyses revealed that general combining ability (GCA) and specific combining ability (SCA) effects were significant for foliar and stem damage traits, indicating that additive and non-additive gene effects conditioned resistance to B. fusca and C. partellus. Sorghum lines ICSA 464, ICSB 474, ICSB 464 and ICSA 472 and ICSB 473 exhibited desirable high negative GCA effects to B. fusca and C. partellus. These parents could be used in development of sorghum with dual resistance to B. fusca and C. partellus thus contributing to sustainable integrated management of these two stem borer species in sorghum via host plant resistance management.
Keywords: Busseola fusca; Chilo partellus; Combining ability; Gene action